Realization of high-efficiency fluorescent organic light-emitting diodes with low driving voltage - Amin Salehi (Nature Portfolio, 2019)
Though organic light-emitting diodes (OLEDs) with electroluminescence at sub-bandgap voltages have been reported, realizing high efficiency in such a device is difficult. Here, the authors report high efficiency sub-bandgap OLEDs featuring organic molecules with large singlet-triplet splitting.